Amino-functionalized basic catalysts with MIL-101 structure - Hartmann, Martin; Fischer, Marcus (Microporous and Mesoporous Materials, 2012)
Metal-organic framework (MOF) materials have only been scarcely explored for applications in heterogeneous catalysis in recent years. In addition to the use of MOFs as supports for the deposition of highly dispersed metal particles, the incorporation of active centers such as coordinatively unsaturated metal sites and the functionalization of the organic linkers with acidic or basic groups seem to be most promising. In our contribution, three different MOFs carrying amino groups at their organic linkers, namely Fe-MIL-101-NH2 (S-BET = 3438 m(2) g(-1)), Al-MIL-101-NH2 (S-BET = 3099 m(2) g(-1)) and CAU-1 (S-BET = 1492 m(2) g(-1)), were synthesized and tested in the Knoevenagel condensation of benzaldehyde with malononitrile and with ethyl cyanoacetate, respectively. It is shown that the expected products benzylidenemalononitrile (BzMN) and ethyl alpha-cyanocinnamate (EtCC) are formed with selectivities exceeding 99% and yields of 90 to 95% after 3 h (for BzMN). Due to the very small pore windows of CAU-1 (0.3 to 0.4 nm) the reaction proceeds much slower over this catalyst in comparison to the amino-MIL-101 derivatives, which possess open pore windows of up to 1.6 nm. Moreover, the catalyst Al-MIL-101-NH2 is recyclable without significant loss of activity. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Metal-organic frameworks; Heterogeneous base catalysis; Amino-catalysts; Knoevenagel condensation

Direct synthesis of non-breathing MIL-53(Al)(ht) from a terephthalate-based ionic liquid as linker precursor - Fischer, Marcus; Schwegler, Johannes; Paula, Carolin; Schulz, Peter; Hartmann, Martin (Dalton Transactions, 2016)
An organic imidazolium salt of terephthalic acid has been utilized as a linker precursor for the synthesis of an aluminum-based metal organic framework (MOF) with MIL-53(ht) structure. This material shows the predicted porosity in terms of nitrogen and hydrogen sorption without exhibiting the breathing effect typical for MIL-53 (Al) materials.

Immobilization of Aspergillus sp. laccase on hierarchical silica MFI zeolite with embedded macropores - Tocco, Davide; Wisser, Dorothea; Fischer, Marcus; Schwieger, Wilhelm; Salis, Andrea; Hartmann, Martin (Colloids and Surfaces B: Biointerfaces, 2023)
Laccase from Aspergillus sp. (LC) was immobilized on functionalized silica hierarchical (microporous-macroporous) MFI zeolite (ZMFI). The obtained immobilized biocatalyst (LC#ZMFI) was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (ATR-FTIR), N2 adsorption/desorption isotherms, solid-state NMR spectroscopy and thermogravimetric analysis (TGA) confirming the chemical anchoring of the enzyme to the zeolitic support. The optimal pH, kinetic parameters (KM and Vmax), specific activity, as well as both storage and operational stability of LC#ZMFI were determined. The LC#ZMFI KM and Vmax values amount to 10.3 µM and 0.74 µmol·mg−1 min−1, respectively. The dependence of specific activity on the pH for free and immobilized LC was investigated in the pH range of 2–7, The highest specific activity was obtained at pH = 3 for both free LC and LC#ZMFI. LC#ZMFI retained up to 50 % and 30 % of its original activity after storage of 21 and 30 days, respectively. Immobilization of laccase on hierarchical silica MFI zeolite allows to carry out the reaction under acidic pH values without affecting the support structure.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Enzyme activity; Enzyme immobilization; Hierarchical porous materials; Laccase; Zeolite

Investigation of the optimum conditions for adsorptive hydrogen storage - Glante, Stephan; Fischer, Marcus; Hartmann, Martin (Emergent Materials, 2021)
Cryogenic adsorption using microporous materials is one of the emerging technologies for hydrogen storage in fuel cell vehicles. Metal-organic frameworks have been identified as suitable adsorbents exhibiting large hydrogen sorption at 77 K. With respect to technical realization, in this work, the deliverable capacity at the optimal storage temperature was determined for a series of MOFs in comparison to zeolite Ca-A. The deliverable capacity is defined as the amount of hydrogen released between a maximum tank pressure and a minimum back pressure and shows a maximum which defines the optimum operating temperature. This optimum operating temperature depends on the pore size of the adsorbent and the chemical properties of the surface. A number of materials are identified that exhibit optimal operating temperatures well above 100 K. A higher optimal storage temperature, however, typically results in a lower deliverable capacity.
CRIS-Team WoS Importer:2021-07-23

One-Step Synthesis of MIL-53(Al)/Boehmite Composites - Schwegler, Johannes; Fischer, Marcus; Paula, Carolin; Schulz, Peter; Hartmann, Martin (Chemie Ingenieur Technik, 2017)
[EMIM][Hbdc]and [EMIM](2)[bdc] were synthesized and successfully used in a one-step synthesis procedure of MIL-53(Al)/boehmite composites with unusual properties. The breathing effect typically observed for MIL-53(Al) is not found and scanning electron microscopy confirms the presence of MIL-53 nanoparticles in a boehmite matrix. The completely different characteristics of this MIL-53 samples in comparison to hydrothermally synthesized MIL-53(Al) clearly demonstrate the tremendous influence of variations of the reagents used for the syntheses of metal-organic framework materials.
Keywords: Ionic liquids; Metal-organic framework; NMR spectroscopy

Optical and electrical studies on the TS defect in 4H-SiC - Lehmeyer, Johannes; Fuchs, Alexander; Li, Zhengming; Bornträger, Titus; Candolfi, Fabio; Schober, Maximilian; Fischer, Marcus; Hartmann, Martin; Neu, Elke; Bockstedte, Michel; Krieger, Michael; Weber, Heiko B. (Journal of Physics D-Applied Physics, 2024)
When annealing a 4H silicon carbide (SiC) crystal, a sequence of optically active defect centers occurs among which the TS center is a prominent example. Here, we present low-temperature photoluminescence analyses on the single defect level. They reveal that the three occurring spectral signatures TS1, TS2 and TS3 originate from one single defect. Their polarization dependences expose three different crystallographic orientations in the basal plane, which relate to the projections of the nearest neighbor directions. Accordingly, we find a three-fold level-splitting in ensemble studies, when applying mechanical strain. This dependency is quantitatively calibrated. A complementary electrical measurement, deep level transient spectroscopy, reveals a charge transition level of the TS defect at 0.6 eV above the valence band. For a future identification, this accurate characterization of its optical and electronic properties along with their response to mechanical strain is a mileston

Perspective on the Use of Ultrasonic Monitoring for In Situ Diagnostics of Zeolite and MOF Crystallization - Ermer, Matthias; Reber, Rebecca; Baser, Hasan-Hüseyin; Fischer, Marcus; Schwieger, Wilhelm; Hartmann, Martin (Crystal Growth and Design, 2023)
The investigation and understanding of the underlying mechanisms for the crystallization of molecular sieve materials, such as metal-organic frameworks (MOFs) and zeolites, have received increasing interest in recent years. This is mainly because improvements of the corresponding equipment were made that are essential for in situ diagnostics. In contrast to classical techniques, such as X-ray diffraction and neutron scattering, nuclear magnetic resonance, or infrared and Raman spectroscopy, ultrasonic monitoring has not received proper attention. Thereby, especially for zeolites, important insights have been gained with this technique already. However, for MOFs, the number of publications dealing with in situ US monitoring is still limited. Therefore, this perspective gives an overview of the topic of in situ monitoring of crystallization of zeolites and MOFs and highlights the work that has been done so far by ultrasonic monitoring. Furthermore, we state benefits and current challenges for further establishing ultrasonic monitoring as a tool for the investigation of crystallization processes.
CRIS-Team Scopus Importer:2023-07-21

The effect of mesoporous bioactive glass nanoparticles incorporating various metallic ions (Cu, Zn, Mn, Te) on wound healing - Pourshahrestani, Sara; Zeimaran, Ehsan; Janko, Christina; Alexiou, Christoph; Kerpes, Andrea; Würz, Adrian; Fischer, Marcus; Kaňková, Hana; Hartmann, Martin; Boccaccini, Aldo R. (Materials Advances, 2024)
Recently, mesoporous bioactive glasses (MBGs) as microparticles or nanoparticles (MBGNs) aroused a great interest owing to their high textural properties and capability to be incorporated with biologically active ions desirable for different stages of wound healing. Considering therapeutic effects of two well-recognized elements (copper and zinc) as well as two less-common elements (manganese and tellurium), in this study, different concentrations of these elements were incorporated into SiO2-CaO MBGNs and their potential for wound healing applications was assessed in vitro. While at a concentration of 5 mg ml−1, the extracts of some MBGNs reduced E. coli and S. aureus bacteria viabilities, normal human dermal fibroblast (NHDF) cell viabilities were negatively affected with extracts of Cu-MBGNs and Te-MBGNs. The nanoparticles also affected hemolysis in a donor-dependent manner and the incorporation of Te into the MBGNs networks increased the hemolysis ratio to more than 5%. Moreover, some of the nanoparticles at concentration of 1 mg ml−1 shortened activated partial thromboplastin time (aPTT) insignificantly compared to pure platelet poor plasma. At higher concentrations of therapeutic elements, the extracts of nanoparticles resulted in the significant slower migration of NHDF cells in the scratch area. The effects of the nanoparticles and their extracts on blood coagulation and NHDF cell migration are thus dependent on the composition and/or applied concentration of nanoparticles. The present results provide information for the design of MBGN compositions of interest for wound healing and highlight the importance of optimization of the nanoparticles dosage and therapeutic ion concentration for acceleration of the wound healing process.
CRIS-Team Scopus Importer:2024-08-09

UiO-66 and hcp UiO-66 Catalysts Synthesized from Ionic Liquids as Linker Precursors - Ermer, Matthias; Mehler, Julian; Rosenberger, Björn; Fischer, Marcus; Schulz, Peter; Hartmann, Martin (ChemistryOpen, 2020)
Using ionic liquids (ILs) as linker precursors, the well-known metal-organic framework (MOF) UiO-66 (Universitetet i Oslo) and the recently reported MOF hcp UiO-66 (hexagonal closed packed) have been successfully synthesized and characterized. The advantage of the applied novel synthesis approach is an economically and environmentally benign work-up procedure, due to the better solubility of the IL. Additionally, the reactivity of the terephthalate anions is increased compared to terephthalic acid, resulting in faster MOF formation with an increased amount of defects in the MOF structure. In order to explore to the influence of defects on the catalytic performance, the cyclisation of citronellal to isopulegol was employed as test reaction. The activity of hcp UiO-66 and fcc UiO-66 (face centered cubic) is improved compared to other MOF or zeolite based catalysts, while the selectivity is similar.
Keywords: UiO-66; metal-organic frameworks; ionic liquids; US damping; citronellal cyclization

Utilizing EPR spectroscopy to investigate the liquid adsorption properties of bimetallic MIL-53(Al/Cr) MOF - Thangavel, Kavipriya; Folli, Andrea; Fischer, Marcus; Hartmann, Martin; Murphy, Damien M.; Pöppl, Andreas (RSC Advances, 2024)
The flexibility of the MIL-53(M) metal-organic framework (MOF) has been elucidated through various characterization methodologies, particularly in gas and liquid adsorption processes. However, to the best of our knowledge, there has been no prior electron paramagnetic resonance (EPR) characterization of liquid-phase adsorption in the MOF MIL-53(M), which offers insights into local geometric changes at the oxygen octahedron containing the metal ions of the framework. In this study, we investigate, for the first time, the pore transformations within the MIL-53(Al0.99Cr0.01) framework during liquid-phase adsorption using EPR spectroscopy. Our investigation concentrates explicitly on the adsorption of pure solvents, including water, methanol, ethanol, isopropanol, pyridine, and mixed water/methanol phases. The EPR spectroscopy on the (Al0.99Cr0.01) MOF has allowed us to witness and comprehend the transitions between the narrow pore and large pore phases by examining changes in the zero-field splitting parameters of the S = 3/2 Cr(iii) species. Of all the solvents examined, a robust and distinct spectral feature observed during methanol adsorption unequivocally indicates the pore opening.
CRIS-Team Scopus Importer:2024-04-26